2013
DOI: 10.4103/0253-7613.106434
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective effect of Saraca indica against cyclophosphamide induced cardiotoxicity in rats: A biochemical, electrocardiographic and histopathological study

Abstract: Objectives:Cardioprotective activity of alcoholic extract of Saraca indica (SI) bark was investigated against cyclophosphamide induced cardiotoxicity.Materials and Methods:Cardiotoxicity was induced in Wistar rats by administering cyclophosphamide (200 mg/kg, i.p.) single injection on first day of experimental period. Saraca indica (200 and 400 mg/kg, p.o.) was administered immediately after administration of cyclophosphamide on first day and daily for 10 days. The general observations and mortality were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
53
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 20 publications
(21 reference statements)
9
53
0
Order By: Relevance
“…Similar to our study in many other studies [11,16,26] there was seen an increasing level of CK-MB when treated with CYP. Our biochemical data has been expressed in the same line with other studies which observed a significant increase in AST and CK-MB levels [25,29,32]. After using the dose of 25, 50, 100 mg/kg HT plus CYP; it was resulted in a clear decrease in AST and CK-MB levels compared to the CYP group (Figure 4, 5, table 1).…”
Section: Tocsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to our study in many other studies [11,16,26] there was seen an increasing level of CK-MB when treated with CYP. Our biochemical data has been expressed in the same line with other studies which observed a significant increase in AST and CK-MB levels [25,29,32]. After using the dose of 25, 50, 100 mg/kg HT plus CYP; it was resulted in a clear decrease in AST and CK-MB levels compared to the CYP group (Figure 4, 5, table 1).…”
Section: Tocsupporting
confidence: 90%
“…Overproduction of reactive oxygen species leads to the oxidative stress, DNA injury, cellular membrane impairment and necrosis in cells and tissues [27]. Also, in some other researches it was observed that CYP quickly damages membranes by lipid peroxidation and results in the loss of myocardial membrane integrity and function [28,29]. CYP induced cardiotoxicity has been implicated to an increase in the generation of reactive oxygen species, which impair the cardiac tissue by exceeding the oxygen radical detoxifying capacity of cardiac mitochondrial cells [30].…”
Section: Discussionmentioning
confidence: 99%
“…with saline solution for 5 consecutive days, one hour after the last dose; rats were injected with a single dose of CP (200 mg/kg, i.p.) (Viswanatha et al, 2013); Group IV: rats were pretreated with NAC (200 mg/kg) for 5 days, 1 h after the last dose; rats were injected with CP (200 mg/kg). Twenty-four hours after the last treatment, the blood was collected by cardiac puncture from the ether anesthetized rats.…”
Section: Experimental Designmentioning
confidence: 99%
“…The groups treated as follows. The group I was kept as control, group II was given CYP at a single intraperitoneal dose of (200 mg/kg body weight) on the first day of the experiment according to [12], group III was administered CYP and Lac, group IV orally administrated Lac only (0.5%) in drinking water during the 21 days of the experiment according to [13], Group V treated with CYP and levamisole. Group VI orally administrated levamisole at a dose of (2.5 mg/kg body weight) according to [14].…”
Section: Experimental Designmentioning
confidence: 99%